Giant pedunculated lipofibroma of the thigh. Issue 3 (28th March 2023) - Suleiman, Jamil; Suleman, Mujaheed; Amsi, Patrick; Minja, Peter; Lodhia, Jay
ABSTRACT: Pedunculated lipofibroma is a rare form of nevus lipomatous cutaneous superficialis. They are usually solitary lesions found around the thighs, buttocks and trunk; thought to have a predilection for pressure areas. There are two types of lipofibromas; sessile or pedunculated. They are mostly asymptomatic but can cause symptoms as they grow larger affecting daily activities. Treatment is not indicated in smaller lesions, except for cosmetic purposes. Herein we present this rare benign lesion with an unusually large size.